Concessões recíprocas por meio de negociação coletiva: constitucionalidade sob a ótica de princípios clássicos do direito do trabalho - Cunha, Matheus de Oliveira (2024)
This dissertation aims to analyze the evolution of trade union legislation, studying the structure of the union in collective bargaining and the functions of the union. After the legal analysis of collective labor law, this dissertation will analyze the rights of relative and absolute unavailability to justify the constitutionality of reciprocal concessions through the collective instrument from the perspective of classic labor law principles. Therefore, the proposal refers to the study of the absence of violation of the classic principles in Labor Law of rights of relative unavailability contextualized to the reality of private initiative to be made more flexible through reciprocal concessions in collective bargaining